Implementation of Environmental Education in Improving The Environmental Ethics of Madrasah Ibtidaiyah Students To Support SDGs 2030 - Aan Fadia Annur; Ratna Sari; Muhammad Maskur Musa (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Madrasah Ibtidaiyah (MI) as an educational institution has an important and strategic role in implementing environmental education for its students so that it can improve students' environmental ethics as a form of support for the SDGs 2030. The purpose of this research is to describe the concept and implementation of environmental education in MI and its support for SDGs 2030. This study is qualitative, with field research being conducted in two MI, namely MI NU Rowolaku and MIN Pekalongan. Data obtained by using the methods of observation, interviews, and documentation The data obtained was then analyzed using Miles and Huberman's qualitative analysis method, which included data collection, data reduction, data presentation, and verification or drawing conclusions. The results showed that MI NU Rowolaku, which has not yet received the status of an adiwiyata school, already has a simple concept of environmental education, but its implementation is good enough so that its carrying capacity for sustainable development goals is classified as moderate. Meanwhile, MIN Pekalongan, which already holds the title of Adiwiyata school, has a clear and measurable concept of environmental education and excellent implementation, so that it has the carrying capacity for sustainable development goals in the high category.